Review: Exhibition Catalogue on Experimental Archaeology by Mamuz - Roeland Paardekooper (EXARC Journal)
The Mamuz Schloss Asparn/Zaya, Austria, is best known for its archaeological open-air site with reconstructed buildings and an active experimental archaeology program. In 2021, MAMUZ designed a traveling exhibition on experimental archaeology, in collaboration with EXARC, who assisted with the provision of experimental archaeologists. Therefore, many of the authors of the exhibition are EXARC members or had previously presented at EXARC conferences.